Penerapan Asas Serentak Tindak Pidana Narkotika dan Pencucian Uang di Pengadilan Tinggi Aceh - Alfian Aulia Rosyadha; Ocna Nusrilia; Bagus Wicaksono; Dariyatmi; Sinta Ana Pramita (Warmadewa Press, 2022)
Imprisonment for a certain period of time may not exceed 20 years as stipulated in Article 12 paragraph 4 of the Criminal Code. the rules for concurrent criminal acts are regulated in a limited manner in Articles 63-70 of the Criminal Code so that the conviction of Abdullah Bin Zakaria in the case of money laundering and narcotics crimes carried out separately is not in accordance with the provisions of the Criminal Code. This study aims to determine the application of the legal principle of concurrent criminal acts in the criminal law system in Indonesia, to determine the principle of concurrent criminal acts in criminalizing Narcotics Crimes and Money Laundering Crimes in Aceh Province. This research uses normative legal research methods by examining positive legal principles related to concurrent criminal acts and approaches. The data used in this research is secondary data which includes official documents, books, and research results in the form of reports. Based on the studies that have been carried out, it is proven that the decision of the Banda Aceh High Court is not in accordance with the provisions stipulated in the Criminal Code. In this decision, Abdullah Bin Zakaria must serve a prison sentence of more than 20 Year. Therefore, it is expected that related parties who are included in the Criminal Justice System apply provisions regarding Concurrent criminal acts in the Crime of Money Laundering and Narcotics Crime.